Using games to ignite teens’ civic and social and emotional learning - Rivers, Susan E.; Bertoli, Michelle C. (Frontiers in Education, 2024)
National trends indicate a pressing need for more impactful civics and history instruction in U.S. secondary education settings. To address this need, we developed an innovative, game-based curriculum, called iThrive Sim, that uses tech-supported role-plays and evidence-based civics and social and emotional learning practices to support high school students in engaging with and comprehending civics and history texts and concepts while developing their social-emotional skills. In this article we describe the need, rationale, and co-design process for this game-based curriculum, its theoretical underpinnings, and its advantages for adolescent learners. We review preliminary pilot and playtesting data that demonstrate initial support for its efficacy and feasibility. Finally, we discuss barriers and additional enhancements and supports that could aid in confirming efficacy and scaling the approach.